The first human case of neuroinvasive West Nile virus infection identified in Cyprus - Niki I. Paphitou; Aristomenis Tourvas; Dora Floridou; Jan Richter; Christina Tryfonos; Christina Christodoulou (Elsevier, 2017)
West Nile virus infection can pose a diagnostic challenge to clinicians, especially in geographic areas where human cases of this disease have never been encountered before. In August 2016, the first human case of West Nile virus infection was diagnosed in Cyprus. An elderly non immunosuppressed patient with a history of recent travel, presented with a clinical picture of rapidly progressing ascending paralysis mimicking Guillain-Barré syndrome. Neuroinvasive West Nile virus disease was diagnosed by detecting West Nile virus nucleic acid in the patient's cerebrospinal fluid. Public health measures were taken raising awareness regarding this disease and its prevention. Clinical vigilance to consider West Nile virus as a possible emerging pathogen in the appropriate clinical setting is warranted and could benefit individual patients. Keywords: West Nile virus, Public health, Neuroinvasive disease, Cyprus, Emerging diseases